2001
DOI: 10.1034/j.1600-0412.2001.080005402.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal hematological status and risk of low birth weight and preterm delivery in Nepal

Abstract: Severe maternal anemia, particularly in the first trimester, was significantly associated with adverse pregnancy outcome. Low maternal age, height or body mass index also increased the risk of low birth weight. Improvements in the nutritional status of young Nepali women could contribute to improved health among their infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
58
1
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 20 publications
8
58
1
1
Order By: Relevance
“…28 Physiological plasma volume expansion might be necessary and even beneficial during pregnancy, 33 but, as we found, severe anemia might have adverse effects as found by others. [34][35][36][37] We found an association between severe anemia and LBW when assessing Hb in the third trimester of pregnancy. Villar and Belizan 38 found that negative factors for fetus' growth around the 30th week of gestation resulted in a disproportionately growth-retarded infant.…”
Section: Discussionmentioning
confidence: 92%
“…28 Physiological plasma volume expansion might be necessary and even beneficial during pregnancy, 33 but, as we found, severe anemia might have adverse effects as found by others. [34][35][36][37] We found an association between severe anemia and LBW when assessing Hb in the third trimester of pregnancy. Villar and Belizan 38 found that negative factors for fetus' growth around the 30th week of gestation resulted in a disproportionately growth-retarded infant.…”
Section: Discussionmentioning
confidence: 92%
“…However, a number of studies have revealed an increased risk of low birth weight (7)(8)(9)12,36), preterm birth (7,8,36) and stillbirth (10,11) associated with anemia in pregnancy. The results of past studies greatly depend on the definition of anemia, the time when hemoglobin was measured and potential confounders used for adjustment.…”
Section: Discussionmentioning
confidence: 99%
“…7 Morbidity pattern is in accordance with studies done in Bangladesh 8 and Netherlands 9 but different than one study. 10 Repeated pregnancy is also contributing factor for poor nutritional status of the mother. All these factors deplete the micronutrient stores of the mother, to the extent that she becomes anaemic even in the first trimester.…”
Section: Discussionmentioning
confidence: 99%